MORAL DIMENSION OF HUMAN ESSENCE FROM THE PERSPECTIVE OF THE PRIEST - S.A. Batrak; V.O. Batrak (Academy of Cognitive and Natural Sciences, 2008)
In this article orthodox priest A. Harmash's point of view on the problem of moral establishment of modern man and the influence of system of education is analysed.